Consumers' willingness to Buy CRISPR gene-edited tomatoes: Evidence from a choice experiment case study in Germany - Linde Götz; Miranda Svanidze; Alain Tissier; Alejandro Brand Duran (Sustainability, 2022)
The CRISPR gene-editing (GE) breeding method is used to increase the resilience of high-yielding tomato cultivars against pests and diseases, reducing crop protection requirements. This study investigated consumers' willingness to buy CRISPR GE tomatoes in a repeated discrete-choice experiment. We observed a strong positive effect of providing information on the CRISPR breeding technology, while the sensory experience of the CRISPR GE tomatoes in a visit to a greenhouse had a rather weak, predominantly negative effect on the participants' willingness to buy CRISPR GE tomatoes. We found that roughly half of the 32 participants demonstrated constant CRISPR GE tomato choices during the experiments, and these participants were mainly employed as scientists. However, the rest of the participants changed their CRISPR GE tomato choices, with the majority showing an increase in their willingness to buy CRISPR GE tomatoes; these "changers" were dominated by non-scientists. Science communication on CRISPR GE breeding technology should target people with little knowledge about the technology, and consumers of organic tomatoes seem to have more specified, stable preferences regarding the technology. Further, scientific information about the CRISPR GE methodology should preferentially be provided when new technology and information about it are not yet widespread and people have not yet formed a strong opinion about the technology.
Keywords: 330; consumers' willingness to buy; discrete-choice experiment; CRISPR gene-edited tomatoes; information intervention; scientific communication